Many-Body and Single-Body Low-Energy Elastic Positron Scattering by Beryllium Atoms: From Ab Initio to Semiempirical Approaches - Marcos V. Barp; Wagner Tenfen; Felipe Arretche (Atoms, 2023)
Positron scattering by beryllium atoms in the low-energy range (≤4.0 eV) was studied within ab initio and semiempirical frameworks. When interpreting the static dipole polarizability and the scattering length as representative quantities of the target and positron–atom correlations, the scattering observables obtained in the ab initio calculation were extrapolated by applying a semiempirical approach. Our results ratify previous ones, since no Ramsauer minimum structures or shape resonances were found in the cross sections. The presence of a (<semantics>e+,Be</semantics>) bound state was also identified as a function of the dipole polarizability.